Parental Job Loss and Children's School Performance - Mari Rege; Kjetil Telle; Mark Votruba (Statistics Norway, Research Department, 2007)
Using Norwegian register data we estimate how children's school performance is affected by their parents' exposure to plant closure. Fathers' exposure leads to a substantial decline in children's graduation-year grade point average, but only in municipalities with mediocre-performing job markets. The negative effect does not appear to be driven by a reduction in father's income and employment, an increase in parental divorce, or the trauma of relocating. In contrast, mothers' exposure leads to improved school performance. Our findings appear to be consistent with sociological "role theories," with parents unable to fully shield their children from the stress caused by threats to the father's traditional role as breadwinner, and mothers responding to job loss by allocating greater attention towards child rearing.
Keywords: I20; J63; J65; 330; educational outcomes; downsizing; job loss; layoffs; plant closure